2014
DOI: 10.1016/j.euroecorev.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of risk attitudes – A revealed preference approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 65 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…In their sample, risk aversion of boys decreases with age, while girls' risk aversion stays constant. 3 Several survey-based investigations have found positive correlation between the risk aversion of adult children and that of their parents (see, e.g., Kimball et al 2009, Dohmen et al 2011, Necker and Voskort 2014, providing evidence for the intergenerational transmission of risk aversion. In addition, experimental studies that correlate decisions in incentivized tasks observe correlations between children's and their parents' risk aversion: Levin and Hart (2003) find a significant correlation between the risk aversion of 6-to 8-year-old children and that of their parents (79% of them mothers).…”
Section: Introductionmentioning
confidence: 99%
“…In their sample, risk aversion of boys decreases with age, while girls' risk aversion stays constant. 3 Several survey-based investigations have found positive correlation between the risk aversion of adult children and that of their parents (see, e.g., Kimball et al 2009, Dohmen et al 2011, Necker and Voskort 2014, providing evidence for the intergenerational transmission of risk aversion. In addition, experimental studies that correlate decisions in incentivized tasks observe correlations between children's and their parents' risk aversion: Levin and Hart (2003) find a significant correlation between the risk aversion of 6-to 8-year-old children and that of their parents (79% of them mothers).…”
Section: Introductionmentioning
confidence: 99%
“…Most relevant to us, empirical studies have found that parents pass on work preferences (Blau et al, 2013;Fernández and Fogli, 2009), employers (Corak and Piraino, 2011), the choice of self-employment (Holtz-Eakin and Dunn, 2000), as well as occupations (Aina and Nicoletti, 2018;Chise et al, 2019;Hederos, 2016) to their children. Moreover, there is also empirical evidence suggesting intergenerational transmission in risk, and possibly other, preferences (Dohmen et al, 2012;Escriche, 2007;Necker and Voskort, 2014), including gender preferences themselves (Farré and Vella, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dohmen et al (2012) analyse the inter-generational transmission of risk and trust attitudes, finding positive evidence of this. Necker and Voskort (2014) investigate whether children and parents show a similar willingness to take risk in their choice of occupation in Germany, and find that fathers' earnings risk is significantly positively related to sons' earnings risk despite that intergenerational transmission is weak in terms of effect size.…”
Section: Literature Reviewmentioning
confidence: 99%